2019
DOI: 10.1093/nar/gkz711
|View full text |Cite
|
Sign up to set email alerts
|

ncRNA-eQTL: a database to systematically evaluate the effects of SNPs on non-coding RNA expression across cancer types

Abstract: Numerous studies indicate that non-coding RNAs (ncRNAs) have critical functions across biological processes, and single-nucleotide polymorphisms (SNPs) could contribute to diseases or traits through influencing ncRNA expression. However, the associations between SNPs and ncRNA expression are largely unknown. Therefore, genome-wide expression quantitative trait loci (eQTL) analysis to assess the effects of SNPs on ncRNA expression, especially in multiple cancer types, will help to understand how risk alleles co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Such differences might be attributed to the different selection pressure in mammals (55) or different regulatory mechanisms underlying these two types of transcripts (56). Furthermore, the current data showed a significant higher enrichment of cancer risk loci in the eQTLs of lncRNAs than in those of mRNA in cancer, which is consistent with a previous study (26).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Such differences might be attributed to the different selection pressure in mammals (55) or different regulatory mechanisms underlying these two types of transcripts (56). Furthermore, the current data showed a significant higher enrichment of cancer risk loci in the eQTLs of lncRNAs than in those of mRNA in cancer, which is consistent with a previous study (26).…”
Section: Discussionsupporting
confidence: 91%
“…While mapping the eQTLs in cancer, we accounted for different confounding effects (such as PEERs, SCNA, DNA methylations). Thus, our model is more stringent than those reported previously (11,26), and the eQTLs directly interfered with the regulome of cancers. In addition, we demonstrated that the genomic landscape of cis-eQTLs of lncRNA was similar to that of the cis-eQTLs of mRNA.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Studies of miRNA abundance across various cell types and tissues have allowed characterizing the extent of genetic regulation of miRNA expression variability, i.e., miRNA expression quantitative trait loci (miR-QTLs), and highlighted the role of genetic variants located in the promoter of the precursor transcript of the miRNA (pri-miRNAs) in shaping inter-individual differences in miRNA expression [8,[12][13][14][15][16][17][18][19]. In the context of immunity, despite increasing evidence that marked population differences exist in the mRNA response to immune challenges [20,21], the extent to which miRNA responses to infection vary across individuals of different ancestry remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of miRNA abundance across various cell types and tissues have allowed the characterization of the extent of genetic regulation of miRNA expression variability, i.e., miRNA expression quantitative trait loci (miR-QTLs), and highlighted the role of genetic variants located in the promoter of the precursor transcript of the miRNA (pri-miRNAs) in shaping inter-individual differences in miRNA expression (Borel et al 2011;Gamazon et al 2012;Parts et al 2012;Lappalainen et al 2013;Siddle et al 2014;Huan et al 2015;Budach et al 2016;Gottmann et al 2018;Li et al 2020). In the context of immunity, despite increasing evidence that marked population differences exist in the mRNA response to immune challenges Quach et al 2016), the extent to which miRNA responses to infection vary across individuals of different ancestry remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%